Determinan Pertumbuhan Sektor Industri di Indonesia Periode 2011 – 2020 - Amar Kurniadi; Riswanti Budi Sekaringsih (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2023)
Industrial growth is an important thing that must be considered in Indonesia's economic development. Good industrial growth will also trigger national economic development, this can be seen in the contribution of the industrial sector to the formation of the national GDP which in 2020 to reach 19.8 percent. To find out the factors that can support industrial growth, this research uses Islamic financing variables, distribution of zakat infaq alms (ZIS), inflation rates, and the BI Rate level on industrial growth in Indonesia.The data used in this study is secondary data in the form of monthly time series data with a period of ten years starting from 2011 to 2020. To determine the effect of the independent variable used on the dependen variable will be analyzed using the Error Correction Model (ECM) method.The results of this study simultaneously variable Islamic financing, distribution of zakat infaq and alms, inflation rate, and the BI Rate together are able to influence industrial growth in Indonesia. Partially shows that Islamic financing positively affectsn industrial growth in Indonesia. The distribution of zakat infaq and alms (ZIS), inflation rate, and BI Rate have do not affectstrial growth in Indonesia.